The strategy of terrorism : how it works, and why it fails - Neumann, Peter R. 1974- (Contemporary terrorism studies, 2008)
This work sets out a comprehensive framework by which to understand terrorism as strategy, contending that terrorism - even of the supposedly nihilist variety - can be viewed as a bona fide method for distributing means to fulfil the ends of policy as a strategy